Prevalence of prehypertension and associated risk factors among Chinese adults from a large-scale multi-ethnic population survey - Tao Xu; Junting Liu; Guangjin Zhu; Junxiu Liu; Shaomei Han (BMC, 2016)
Abstract Background Up to date, most of previous studies about Chinese prehypertension were conducted based on a small sample or in only one province, which could not represent the general population in China. Furthermore, no information on the ethnic difference in prevalence of prehypertension has been reported in China. The aim of this study is to examine the sex-specific, age-specific and ethnic-specific prevalence of prehypertension and associated risk factors in a large-scale multi-ethnic Chinese adult population. Methods The subjects came from a large-scale population survey about Chinese physiological constants and health conditions conducted in six provinces. 47, 495 adults completed blood pressure measurement. Prehypertension was defined as not being on antihypertensive medications and having SBP of 120-139 mmHg and/or DBP of 80-89 mmHg. Odds ratio (OR) and its 95 % confidence interval (CI) from logistic models were used to reflect the prevalence of prehypertension. Results The mean age of all subjects was 43.9 ± 16.8 years. The prevalence of hypertension and prehypertension for all them was 29.5 and 36.4 %, respectively. The prevalence of hypertension and prehypertension for males (33.2 and 41.1 %, respectively) was higher than that for females (27.0 and 33.2 %, respectively), and P < 0.001. The mean age of the subjects was 54.8 ± 14.0 years for hypertensive, 44.0 ± 16.0 years for prehypertensive and 35.3 ± 14.5 years for normotensive. With aging, subjects had more odds of getting prehypertension. Multivariate logistic model indicated that males (OR = 2.076, 95 % CI: 1.952-2.208), laborers with mental work (OR = 1.084, 95 % CI: 1.020-1.152), Yi (OR = 1.347, 95 %CI: 1.210-1.500) and Hui subjects (OR = 1.133, 95 % CI: 1.024-1.253), alcohol drinkers (OR = 1.147, 95 % CI: 1.072-1.228), the generally obese (OR = 2.460, 95 % CI: 2.190-2.763), the overweight (OR = 1.667, 95 % CI: 1.563-1.788), the abdominally obese (OR = 1.371, 95 % CI: 1.280-1.467) and subjects with family history of cardiovascular diseases (OR = 1.132, 95 % CI: 1.045-1.226) had higher prevalence of prehypertension. Subjects with higher educational level (OR = 0.687, 95 % CI: 0.627-0.752 for university) and Miao (OR = 0.753, 95 % CI: 0.623-0.910), Tibetan (OR = 0.521, 95 % CI: 0.442-0.613), Tujia (OR = 0.779, 95 % CI: 0.677-0.898) subjects had lower prevalence. Conclusion High prevalence rate of prehypertension was general in Chinese adults. Many sociodemographic characteristics were significantly associated with prehypertension. There were important clinical significance and public health significance about age-specific, gender-specific and ethnic-specific Chinese prehypertension conditions studies.